2021
DOI: 10.1097/j.jcrs.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens implantation in the absence of capsular support: scleral-fixated vs retropupillary iris-claw intraocular lenses

Abstract: Retropupillary iris-claw IOL implantation provides similar efficacy and equivalent or potentially better safety profile than scleral-fixated IOL implantation in eyes with poor capsular/zonular support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 104 publications
(803 reference statements)
0
5
0
Order By: Relevance
“…Additionally, regarding postoperative complications, in group 1, there were two cases of IOL dislocation, one case of vitreal hemorrhage and one case of hyphema. This may be a consequence of the stress that the iris claw implantation causes on the iris diaphragm, which, in some cases, may be damaged during the enclavation procedure, as already reported in the literature[15]. Bogumiła Sędziak-Marcinek et al[16] recently reported the results of the secondary anterior-chamber implantation of iris claw on a large cohort of 132 patients, describing the procedure to be easier and shorter than posterior chamber iris claw lens fixation, to minimize the risk of postoperative macular edema, intraocular hemorrhagic complications and also retinal detachments with a mild reduction in the number of corneal endothelial cells.…”
mentioning
confidence: 75%
“…Additionally, regarding postoperative complications, in group 1, there were two cases of IOL dislocation, one case of vitreal hemorrhage and one case of hyphema. This may be a consequence of the stress that the iris claw implantation causes on the iris diaphragm, which, in some cases, may be damaged during the enclavation procedure, as already reported in the literature[15]. Bogumiła Sędziak-Marcinek et al[16] recently reported the results of the secondary anterior-chamber implantation of iris claw on a large cohort of 132 patients, describing the procedure to be easier and shorter than posterior chamber iris claw lens fixation, to minimize the risk of postoperative macular edema, intraocular hemorrhagic complications and also retinal detachments with a mild reduction in the number of corneal endothelial cells.…”
mentioning
confidence: 75%
“…The capsular bag could not be saved in most cases. Implantation of AC IOL or sutured IOL to the sclera can cause several complications, such as glaucoma or retinal detachment [9][10] . Cionni et al [5] reported an endocapsular ring with a fixed hook for use in eyes with zonular insufficiency.…”
Section: Resultsmentioning
confidence: 99%
“…S cleral fixation is a major strategy for intraocular lens (IOL) implantation in eyes with inadequate capsular support for the IOL 1 because of previous ocular trauma, severe damage to the capsular bag during cataract surgery, and spontaneous loss of zonular suspension such as in Marfan or pseudo-exfoliation syndrome. 2,3 Compared with iris fixation of anterior chamber IOL, scleral fixation technique has the advantage of fewer complications such as glaucoma, peripheral anterior synechia, and corneal endothelial decompensation.…”
mentioning
confidence: 99%